Trends and patterns of orthognathic surgery in Saudi Arabia: a visualized bibliometric analysis of research output - Alsulaimani, Mahmoud; Hamadallah, Hatem; Aloufi, Aseel; Aljuhani, Fadia; Alhazmi, Rahma; Alsaeedi, Ahmed; Mirah, Mahir (International Journal Of Community Medicine And Public Health, 2024)
This study conducted a bibliometric analysis of orthognathic surgery research from Saudi Arabia between 1994 and 2024 in the Web of Science database. The goal was to evaluate Saudi Arabia’s influence in the field and implications worldwide. Relevant keywords were used without year restrictions to search for articles. Biblioshiny and VOS viewer were used to analyse and visualize the bibliometric data, including total citations, h-index, and number of papers. The results show that Saudi Arabia has significantly increased its orthognathic surgery research production over time, especially in 2021 and 2023. King Saud University and King Abdulaziz University emerged as the leading institutions in number of papers. The most cited work was an expert review on using artificial intelligence for orthodontic diagnosis and planning orthognathic surgeries. This represents meaningful progress in combining technology with orthognathic surgery. Alhammad, Alnofaie, and Al-Sebaei were identified as the most productive individual authors, each authoring around three papers. The bibliographic analysis highlights the need for increased cooperation between Saudi institutions to boost research outputs and advance the application of new technologies in orthognathic surgery. The study serves as a foundation for further developing orthognathic surgery research in Saudi Arabia, which remains one of the few developing nations showing promising potential for growth in this area.